A crítica cinematográfica em O Diário de S. Paulo entre 1968 e 1969: um estudo sobre a experiência dos estudantes da Universidade de São Paulo - Bellinger, Isabella Mitiko Ikawa (2013)
This research is a study of the film section in O Diário de S. Paulo between July 1968 and June 1969. In this year, a group composed by Álvaro Ferreira, Claudio de Andrade (pseudonym initially used by Jean-Claude Bernardet), Djalma Batista, Eduardo Leone, Frida, Ismail Xavier, José Possi Neto, Marília Aires (now Marília Franco), Maurice Politi, Sérvulo Peres Siqueira e Valéria Silveira signed the film criticism in this journal. Most of these students were from the first Cinema s class in ECC-USP (Escola de Comunicações Culturais da Universidade de São Paulo), which later would become ECA-USP (Escola de Comunicações e Artes). Others came from Theater and Journalism. This experience in O Diário de S. Paulo is what we propose to study in this work.